How Norms Matter in Mediation: An Introduction. Issue 4 (31st December 2020) - Hellmüller, Sara; Pring, Jamie; P. Richmond, Oliver
Abstract: International mediators are often tasked to promote liberal norms. However, dilemmas created in diffusing these norms, influenced by the mediators' interaction with the conflict parties and a decline of the liberal international order, have fueled debates about how norms are diffused through mediation, whether mediators should and can promote norms, and what norms they promote. The IR literature provides rich theoretical frameworks on norms, which could help navigate these questions. Yet, mediation scholars have not systematically integrated ideational aspects in their analyses. This Special Issue fills this gap by providing the first comprehensive analysis of how norms matter in mediation. It thereby not only shares novel analytical insights on norms in mediation, but also enriches the conceptualizations of three central notions in the norms literature: the norm diffusion process, the agency of actors, and the nature of the diffused norms.